Peer Quality and the Academic Benefits to Attending Better Schools - Hoekstra, Mark; Mouganie, Pierre; Wang, Yaojing (Journal of Labor Economics, 2018)
Despite strong demand for attending high schools with better peers, there is mixed evidence on whether doing so improves academic outcomes. We estimate the cognitive returns to high school quality by comparing the college entrance exam scores of students in China who were barely above and below high school admission thresholds. Results indicate that while peer quality improves significantly across all sets of admission cutoffs, the only increase in performance occurs from attending tier 1 high schools. Further evidence suggests the returns to high school quality are driven by teacher quality rather than peer quality or class size.